Honour Crime; Factors and Challenges: A Case Study of Khyber Pakhtunkwa Province Pakistan - Bibi, Hamida; Khan, Yunas; Rani, Tabinda (International Journal of Criminology and Sociology, 2021)
The Province of Khyber Pakhtunkhwa, Pakistan has a 35.25 million population and the largest ethnic group is the Pashtun. Society is strongly conservative and loves the strong moral character. This study was an attempt to ascertain the major causes of honour killing in the Province of Khyber Pakhtunkhwa, Pakistan highlighting the legal and institutional framework adopted by the enforcing agencies to overcome it. At the same time, this study will ascertain the factors behind the increase of honour killing and defectiveness in the legal and institutional framework by analysis of available data in the literature that relevant to such killings taking into consideration the racial, religious, historical, and political motives. Lastly Study concluded with substantial recommendations that may be adopted as step forward in eradication of such a tenacious phenomenon.